การปรับสภาพเบื้องต้นของผ้าฝ้ายด้วยโปรตีนถั่วเหลืองสำหรับการย้อมด้วยสีสกัดจากแก่นขนุนและการตกแต่งด้วยน้ำมันลินสีดมาเลเอต - อาณัติ ชีวอาณัติ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The propose of this project was to study the effect of soy protein on the dyeability of jackfruit wood extract (morin dye) and maleated linseed oil on colour fastness of morin-dyed cotton fabric. Firstly, crude soybean milk as a source of soy protein was depolymerized with 5 g/L NaOH at room temperature and then diluted to obtain various solid contents of 5, 10, 15, 20, 25, and 30 g/L. Thus obtained soybean milk was applied onto cotton fabrics by padding. Characterizations including ATR-FTIR and CHNS/O analyzer confirmed that the soy protein was present on the fabric surface and the amount of soy protein reached the optimum level at the applied concentration of 25 g/L as indicated by percent nitrogen content. After that, treated cotton fabric was dyed with jackfruit wood extract (the extract conditions were 1:10 liquor ratio at boiling temperature) at 60˚C for 45 min. It was found that fabric treated with soy protein exhibited an increase in colour strength with an increase in percent soy protein add-on due to the protein–morin dye attraction arising from a number of hydrogen bondings. However, the absorbance value did not decrease as the concentration of soy protein increased, reflecting the surface dyeing phenomenon which typically was associated with poor wash fastness. An improvement of wash fastness was achieved by finishing the morin dyed cotton fabric with maleated linseed oil using pad-cure method. It was observed that the finished cotton fabric with maleated linseed oil exhibited a better colour fastness to wash when compared to unfinished cotton fabric. Due to the change in surface hydrophobicity of linseed oil finished dyed fabric, dye tended to be retained in the fabric during washing, resulting in improved wash fastness.